A randomised clinical trial comparing the 'sniffing' and neutral position using channelled (KingVision®) and non‐channelled (C‐MAC®) videolaryngoscopes. (16th April 2018) - Mendonca, C.; Ungureanu, N.; Nowicka, A.; Kumar, P.
Summary: Head and neck position is one of the factors which can be associated with difficult videolaryngoscopy and tracheal intubation. This prospective randomised clinical trial compared 'sniffing' and neutral positions using a channelled (KingVision ® ) and a non‐channelled (C‐MAC ® D‐blade) videolaryngoscope in 200 adult patients randomly allocated into four groups (KingVision 'sniffing', KingVision neutral, C‐MAC 'sniffing' and C‐MAC neutral). The primary outcome was the ease of tracheal intubation using the modified intubation difficulty scale (mIDS) score. Laryngoscopy time, intubation time, laryngoscopic view using the percentage of glottic opening (POGO) score and success rate of tracheal intubation were secondary outcomes. The median (IQR [range]) modified difficulty scale scores for the four groups, respectively, were 0 (0–1 [0–3]), 0 (0–1 [0–4]), 1 (0–1 [0–5]) and 0 (0–1 [0–3]; p = 0.384). There was no significant difference in laryngoscopy time (p = 0.020), intubation time (p = 0.272) and success rate (p = 0.968) between the groups. The percentage of glottic opening score was lower for C‐MAC neutral group as compared with other three groups (p = 0.01). There was no significant difference in the ease of intubation between the 'sniffing' and the neutral position when using the KingVision and the C‐MAC videolaryngoscopes. Therefore, either of the two positions could be used with these types of videolaryngoscopes, if deemed advantageous for the patient.